Antineoplastic effect of 1α,25(OH)2D3 in spheroids from endothelial cells transformed by Kaposi’s sarcoma-associated herpesvirus G protein coupled receptor - Suares, Alejandra Carolina (2019)
The Kaposi´s Sarcoma-associated Herpes virus G Protein-Coupled Receptor (vGPCR) is a key molecule in the pathogenesis of Kaposi?s sarcoma. Persistent expression and activity of vGPCR is required for NFB pathway activation and tumor maintenance in endothelial cells. We have previously demonstrated that 1α,25(OH)2D3 inhibits vGPCR cell growth, NFB activity and induces apoptosis in a VDR dependent manner. Many types of mammalian cells can aggregate and differentiate into 3-D multicellular spheroids (MCS) when cultured in suspension or a non adhesive environment. Compared to conventional mono-layer cultures (2D-cultures), MCS resemble real tissues better in terms of structural and functional properties. In this study we developed the method to obtain MCS from vGPCR cells in order to test whether MCS respond similar to 2D-cultures during 1α,25(OH)2D3. First, we found that vGPCR MCS started to form after 4 day-growth and reached a diameter of 200 µm at 12 day-growth, whereas cells without vGPCR expression remained in a starry shape. Secondly, vGPCR MCS size and architecture was analyzed during 1α,25(OH)2D3 (0-100 nM, 48 h) incubation. We found that MCS treated with 1 nM of 1α,25(OH)2D3 were compacted and began to disaggregate though no changes in their size were observed, whereas at the higher dose (100 nM) the architecture of MCS was broken. Furthermore, VDR mRNA expression increased significantly and this change was accompanied by a reduction of HIF-1α and an increase of VEGF, p21 and Bim mRNA expression. Finally, Results from Western blot analysis showed that 1α,25(OH)2D3 decreased ERK1/2 and Akt protein phosphorylation. In conclusion, these data have revealed that 1α,25(OH)2D3 inhibits vGPCR MCS proliferation and induces apoptosis similar to vGPCR 2D-cultures.Keywords: Spheroids, vGPCR cells, 1α,25(OH)2D3, anti-proliferative effects.